Type 1 Diabetes and Impaired Awareness of Hypoglycemia Are Associated with Reduced Brain Gray Matter Volumes - Bednarik, Petr; Moheet, Amir A.; Grohn, Heidi; Kumar, Anjali F.; Eberly, Lynn E.; Seaquist, Elizabeth R.; Mangia, Silvia (Frontiers in Neuroscience, 2017)
In this study, we retrospectively analyzed the anatomical MRI data acquired from 52 subjects with type 1 diabetes (26M/26F, 36±11 years old, A1C=7.2%±0.9%) and 50 age, sex and BMI frequency-matched non-diabetic controls (25M/25F, 36±14 years old). The T1D group was further sub-divided based on whether subjects had normal, impaired, or indeterminate awareness of hypoglycemia (n=31, 20, and 1, respectively). Our goals were to test whether the grey matter volumes of selected brain regions were associated with diabetes status as well as with the status of hypoglycemia awareness. T1D subjects were found to have slightly smaller volume of the whole cortex as compared to controls (-2.7%, p=0.016), with the most affected brain region being the frontal lobe (-3.6%, p=0.024). Similar differences of even larger magnitude were observed among the T1D subjects based on their hypoglycemia awareness status. Indeed, compared to the patients with normal awareness of hypoglycemia, patients with impaired awareness had smaller volume of the whole cortex (-7.9%, p=0.0009), and in particular of the frontal lobe (-9.1%, p=0.006), parietal lobe (-8.0%, p=0.015) and temporal lobe (-8.2%, p=0.009). Such differences were very similar to those observed between patients with impaired awareness and controls (-7.6%, p=0.0002 in whole cortex, -9.1%, p=0.0003 in frontal lobe, -7.8%, p=0.002 in parietal lobe, and -6.4%, p=0.019 in temporal lobe). On the other hand, patients with normal awareness did not present significant volume differences compared to controls. No group-differences were observed in the occipital lobe or in the anterior cingulate, posterior cingulate, hippocampus and thalamus. We conclude that diabetes status is associated with a small but statistically significant reduction of the whole cortex volume, mainly in the frontal lobe. The most prominent structural effects occurred in patients with impaired awareness of hypoglycemia as compared to those with normal awareness, perhaps due to the long-term exposure to recurrent episodes of hypoglycemia. Future studies aimed at quantifying relationships of structural outcomes with functional outcomes, with cognitive performance, as well as with parameters describing glucose variability and severity of hypoglycemia episodes, will be necessary to further understand the impact of T1D on the brain.